VLP-ELISA for the Detection of IgG Antibodies against Spike, Envelope, and Membrane Antigens of SARS-CoV-2 in Indian Population - Dilip Kumar; Sourav Singha Roy; Ruchir Rastogi; Kajal Arora; Avinash Undale; Reeshu Gupta; Nupur Mehrotra Arora; Prabuddha K. Kundu (Vaccines, 2023)
Background: Serological methods to conduct epidemiological survey are often directed only against the spike protein. To overcome this limitation, we have designed PRAK-03202, a virus-like particle (VLP), by inserting three antigens (Spike, envelope and membrane) of SARS-CoV-2 into a highly characterized S. cerevisiae-based D-Crypt™ platform. Methods: Dot blot analysis was performed to confirm the presence of S, E, and M proteins in PRAK-03202. The number of particles in PRAK-03202 was measured using nanoparticle tracking analysis (NTA). The sensitivity of VLP-ELISA was evaluated in 100 COVID positive. PRAK-03202 was produced at a 5 L scale using fed-batch fermentation. Results: Dot blot confirmed the presence of S, E, and M proteins in PRAK-03202. The number of particles in PRAK-03202 was 1.21 × 109 mL−1. In samples collected >14 days after symptom onset, the sensitivity, specificity, and accuracy of VLP-ELISA were 96%. We did not observe any significant differences in sensitivity, specificity, and accuracy when post-COVID-19 samples were used as negative controls compared to pre-COVID-samples. At a scale of 5 L, the total yield of PRAK-03202 was 100–120 mg/L. Conclusion: In conclusion, we have successfully developed an in-house VLP-ELISA to detect IgG antibodies against three antigens of SARS-CoV-2 as a simple and affordable alternative test.